An Analysis Of Students’ Errors In Writing Procedure Text At SMA Negeri 9 Maluku Barat Daya - Tutupahar, Narsi Teroci; Lekawael, Rosina F. J.; Hukom, S. J. (Koli Journal : English Language Education, 2022)
The purpose of this research is to examine the errors made by Tenth-Grade students in composing procedure texts at SMA Negeri 9 Weet, Maluku Barat Daya. This place was chosen because the school is the place for PPL researchers and based on previous interviews with the English teacher at the school discussing the process of students writing procedure texts. The participants in this research include 16 students in class X MIA. The aims of this study were (1) to identify the types of errors in procedure text writing, and (2) to determine the most dominant errors. This qualitative research employed a descriptive method, utilizing research instruments to collect, identify, and classify errors based on Dulay’s surface strategies taxonomy. It was delineated by four categories of errors namely omission, addition, misformation, and misordering. The findings indicated that the most dominant error was Misformation with the 35 items (52.23%). The second error executed by students Omission with the 19 items (28.35%). The third error executed by students was Misordering with the 8 items (11.94%). The lowest frequency of error was Addition with the 5 items (7.46%).